A ternary composite nano wave-absorbing material with a hollow double-spherical shell structure, a preparation method and applications thereof

CN117655322BActive Publication Date: 2026-10-27NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311600326.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2026-10-27
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

但目前多元复合材料多以二元材料为主,且在复合材料制备时很难兼顾纳米材料微观结构的设计

Benefits of technology

[0016]本发明以空心双球壳碳化硅-碳为骨架,在其表面添加纳米磁性粒子,构筑多元复合纳米吸波材料。该微纳复合吸波剂特殊的空心双球壳结构结合材料本征特性使得其不仅对电磁波具有良好的损耗吸收能力,并且复合材料的磁介协同作用还有效的扩宽了材料的吸波频段。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117655322B_ABST
    Figure CN117655322B_ABST
Patent Text Reader

Abstract

The application discloses a kind of ternary composite nano wave-absorbing materials with hollow double-sphere shell structure and preparation method and application thereof, belong to material field, preparation method includes: step one, tetraethyl orthosilicate and resorcinol are placed in alkaline solution environment and prepared organic precursor by sol-gel process;Step two, organic precursor is carbonized under high-temperature inert gas, etching, and hollow double-sphere shell is obtained;Step three, hollow double-sphere shell is mixed with Fe 3+ And Co 2+ , citric acid is added to complex Fe 3+ And Co 2+ , then hydrothermal reaction is carried out, and hollow double-shell silicon carbide@carbon@metal oxide composite material is obtained;Step four, hollow double-shell silicon carbide@carbon@metal oxide composite material is subjected to carbothermal reduction reaction, and hollow double-sphere shell ternary composite nano wave-absorbing material SiC@C@FeCo is obtained.The application material has good loss absorption capacity, and simultaneously widens the wave-absorbing frequency band of material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials and relates to a microwave absorbing material, particularly a ternary composite nano-microwave absorbing material with a hollow double-spherical shell structure, its preparation method, and its application. Background Technology

[0002] In the 5G era, the rapidly developing electromagnetic waves, while promoting technological progress, have also brought a series of unavoidable electromagnetic radiation pollution problems. To reduce the harm of electromagnetic radiation to human health and avoid electromagnetic interference between electronic devices, it is necessary to research a series of lightweight absorbing materials with high loss and high absorption of electromagnetic waves. In recent years, multi-component composite nano-microwave absorbers with special cavity structures have been widely studied due to their lightweight nature and the synergistic effect of multiple loss mechanisms. Electromagnetic wave absorbing materials can utilize their intrinsic properties and special micro-nano structures to dissipate incident electromagnetic waves by converting them into heat or other forms of energy. Compared to electromagnetic shielding materials, this approach can eliminate electromagnetic pollution at its source. It is also environmentally friendly and therefore has broad application prospects.

[0003] The two main loss mechanisms of current microwave absorbing materials are electrical loss and magnetic loss. Among materials with only electrical loss, carbon-based materials, with their excellent conductivity, allow incident electromagnetic waves to dissipate within the material through conductivity loss, leading to their rapid development in the microwave absorbing field. However, the high conductivity of carbon-based materials easily leads to impedance mismatch, thus limiting their development. Semiconductor materials, due to their stable physical and chemical properties, such as acid and alkali resistance, high temperature resistance, and high strength, have been extensively studied in the field of high-temperature microwave absorption. However, the loss mechanism of semiconductor materials is mainly polarization loss, resulting in poor loss capability. Therefore, they are often combined with highly conductive carbon-based materials to improve the impedance matching of the carbon-based materials. Materials with magnetic loss as the loss mechanism commonly include ferrite materials, metals, metal alloys, and carbonyl iron. The introduction of magnetic loss mechanisms can not only further optimize the impedance matching of materials but also compensate for the insufficient low-frequency loss capability of materials with only dielectric loss, effectively expanding the bandwidth of microwave absorbing materials and enhancing their loss capability. Therefore, multi-component composite nanomaterials are an effective way to prepare high-strength, broadband microwave absorbing materials. However, most multi-component composite materials are currently binary materials, and it is difficult to consider the design of the microstructure of nanomaterials during the preparation of composite materials. Furthermore, due to the introduction of multiple components, the interactions between the components within the material, such as the formation of new heterogeneous interfaces, and the atomic migration and doping energy at the heterogeneous interfaces, also have a certain impact on the electromagnetic parameters of the material. Summary of the Invention

[0004] This invention provides a ternary composite nano-absorbing material with a hollow double-spherical shell structure, its preparation method, and its application, in order to overcome the defects of the prior art.

[0005] To achieve the above objectives, this invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-shell structure, characterized by the following steps: Step 1, preparing an organic precursor (silicon dioxide@phenolic resin) by reacting tetraethyl silicate and resorcinol in an alkaline solution environment to undergo a sol-gel process; Step 2, carbonizing the organic precursor obtained in Step 1 under a high-temperature inert gas environment, and etching the carbonized product with sodium hydroxide solution to obtain a hollow double-shell (silicon carbide@carbon); Step 3, combining the hollow double-shell obtained in Step 2 with Fe... 3+ and Co 2+ The mixture was prepared using a strategy similar to that used in sol-gel precursor solution synthesis, with the addition of citric acid to treat Fe. 3+ and Co 2+ The mixture is complexed, and then the pH is adjusted to alkaline for hydrothermal reaction to obtain a hollow double-shell silicon carbide@carbon@metal oxide composite material. Step four: The hollow double-shell silicon carbide@carbon@metal oxide composite material obtained in step three is subjected to a carbothermal reduction reaction. The reducing property of the outer carbon shell is used to reduce the outer metal oxide to metal alloy nanoparticles, and finally a hollow double-shell ternary composite nano-absorbing material SiC@C@FeCo is obtained.

[0006] Furthermore, the present invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, which may also have the following characteristics: wherein, the specific method of step one is as follows: placing tetraethyl silicate in a solution containing anhydrous ethanol, deionized water and ammonia and stirring for 20-40 min, then dissolving resorcinol in formaldehyde solution and adding it to the solution containing tetraethyl silicate, and continuing to stir for 20-30 h to obtain an organic precursor.

[0007] Furthermore, the present invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, which may also have the following characteristics: wherein the ratio of tetraethyl orthosilicate to resorcinol is 4-6 ml: 0.5-1 g.

[0008] Furthermore, the present invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, which may also have the following characteristics: wherein, in step two, the carbonization method is as follows: the temperature is increased from room temperature to 550°C at a heating rate of 2°C / min, and held at 550°C for 2 hours; then the temperature is increased from 550°C to 1350°C at a heating rate of 2°C / min, and held at 1350°C for 4 hours.

[0009] Furthermore, the present invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, which may also have the following characteristics: wherein, in step two, the concentration of the sodium hydroxide solution is 5 mol / L and the etching time is 72 h.

[0010] Furthermore, this invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, which may also have the following characteristics: wherein, in step three, the metal ions are cobalt nitrate nonahydrate and ferric nitrate hexahydrate; the citric acid is citric acid monohydrate; Fe 3+ Co 2+ The molar ratio of citric acid monohydrate to Fe is 2:1:3; hollow double-shell structure with Fe 3 + The dosage ratio is 20-40 mg : 0.0015 mol.

[0011] Furthermore, the present invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, which may also have the following characteristics: in step three, the temperature of the hydrothermal reaction is 180-250℃ and the time is 4-12h.

[0012] Furthermore, the present invention provides a method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, which may also have the following characteristics: wherein, in step four, the specific method of the carbothermic reduction reaction is to raise the temperature from room temperature to 800℃ at a heating rate of 2℃ / min, and hold at 800℃ for 2h.

[0013] This invention also provides a ternary composite nanomaterial with a hollow double-shell structure prepared by the above-described method. The absorbing material has a double-shell hollow structure; the first layer is a semiconductor silicon carbide layer, the second layer is a conductive carbon layer, and the third layer is a magnetic metal alloy; the first semiconductor silicon carbide layer is a hollow spherical shell structure, the second conductive carbon layer covers the first layer, and the third layer of magnetic metal alloy nanoparticles is embedded on the surface of the shell; the first semiconductor material is SiC; the second conductive material is C; the third magnetic metal alloy nanoparticles are FeCo; the inner hollow diameter is 250 nm to 300 nm, the total thickness of the double shell is approximately 20 nm, and the diameter of the magnetic alloy nanoparticles is distributed between 20 nm and 50 nm.

[0014] The present invention also provides the application of the above-mentioned ternary composite nano-absorbing material with hollow double spherical shell structure in microwave absorption.

[0015] The beneficial effects of this invention are as follows:

[0016] This invention uses a hollow double-shell silicon carbide-carbon framework, with nano-magnetic particles added to its surface to construct a multi-component composite nano-absorbing material. The unique hollow double-shell structure of this micro / nano composite absorber, combined with the material's intrinsic properties, not only gives it excellent loss absorption capability for electromagnetic waves, but the synergistic effect of the composite material's magnetic properties also effectively broadens the material's absorption frequency band.

[0017] Specifically, this invention utilizes the stable chemical and physical properties of semiconductor materials as the inner framework support material, the reducing properties and high conductivity of the outer carbon coating, and the unique hollow double-shell structure of the materials. This allows for the introduction of a third component onto the spherical shell surface while simultaneously constructing rich heterogeneous interfaces, thus enabling a better synergistic effect between the material's structural and component advantages. Furthermore, by controlling the hydrothermal insulation time, the heterogeneous interfaces formed between different components can be controlled, thereby achieving high-intensity absorption of electromagnetic waves. Attached Figure Description

[0018] Figure 1 This is a scanning electron microscope image of the hollow double-spherical shell SiC@C nanoparticles obtained in step two of Example 2;

[0019] Figure 2 This is the XRD pattern of the hollow double-spherical shell SiC@C nanoparticles obtained in step two of Example 2;

[0020] Figure 3 This is a high-magnification transmission electron microscope image of the hollow double-spherical shell ternary composite nano-absorbing material SiC@C@FeCo prepared in Example 2;

[0021] Figure 4 This is the XRD pattern of the hollow double-spherical shell ternary composite nano-absorbing material SiC@C@FeCo prepared in Example 2;

[0022] Figure 5 This is a graph showing the electromagnetic wave absorption performance of the hollow double-spherical shell ternary composite nano-absorbing material prepared in Example 2. Detailed Implementation

[0023] The present invention will be further described below with reference to specific embodiments.

[0024] Example 1

[0025] This embodiment provides a ternary composite nano-absorbing material with a hollow double-spherical shell structure. The preparation method includes the following steps:

[0026] Step 1: Place 4.56 ml of tetraethyl silicate in a solution containing 100 ml of anhydrous ethanol, 14 ml of deionized water, and 6 ml of ammonia and stir for 25 min. Then, completely dissolve 0.8 g of resorcinol in 4.48 ml of formaldehyde solution (37 wt%) and add it to the solution containing tetraethyl silicate. Continue stirring and reacting for 24 h. The resulting organic solution is washed three times by centrifugation with deionized water and three times by centrifugation with ethanol to obtain the organic precursor.

[0027] Step 2: The organic precursor obtained in Step 1 was placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min, and held at 550°C for 2 hours. Then, the temperature was increased from 550°C to 1350°C at a rate of 2°C / min, and held at 1350°C for 4 hours. The product was then etched in a 5 mol / L sodium hydroxide solution for 72 hours. After etching, the product was washed with deionized water by centrifugation until the pH was neutral, dried, and the hollow double-shell product was collected.

[0028] Step 3: Place 30 mg of the hollow double-shell obtained in Step 2, 0.606 g of ferric nitrate nonahydrate, 0.218 g of cobalt nitrate hexahydrate, and 0.472 g of citric acid monohydrate in 50 ml of deionized water. Add ammonia to adjust the pH to 9-10. After stirring for 20 min, place the mixture in a 100 ml polytetrafluoroethylene liner for hydrothermal reaction. The hydrothermal reaction temperature is 200℃, and the hydrothermal holding time is adjusted to 4 h. After the hydrothermal reaction is completed, wash the mixture three times with deionized water and once with alcohol. Dry the mixture in an oven to obtain the hollow double-shell silicon carbide@carbon@metal oxide composite material.

[0029] Step 4: Place the hollow double-shell silicon carbide@carbon@metal oxide composite material obtained in Step 3 into a high-temperature tube furnace and heat it from room temperature to 800℃ at a heating rate of 2℃ / min. Hold it at 800℃ for 2 hours. Utilize the reducing properties of the outer carbon shell to reduce the outer metal oxide to FeCo alloy nanoparticles, and finally obtain the hollow double-shell ternary composite nano-absorbing material SiC@C@FeCo.

[0030] Example 2

[0031] This embodiment provides a ternary composite nano-absorbing material with a hollow double-spherical shell structure. The preparation method includes the following steps:

[0032] Step 1: Place 4.56 ml of tetraethyl silicate in a solution containing 100 ml of anhydrous ethanol, 14 ml of deionized water, and 6 ml of ammonia and stir for 25 min. Then, completely dissolve 0.8 g of resorcinol in 4.48 ml of formaldehyde solution (37 wt%) and add it to the solution containing tetraethyl silicate. Continue stirring and reacting for 24 h. The resulting organic solution is washed three times by centrifugation with deionized water and three times by centrifugation with ethanol to obtain the organic precursor.

[0033] Step 2: The organic precursor obtained in Step 1 was placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min, and held at 550°C for 2 hours. Then, the temperature was increased from 550°C to 1350°C at a rate of 2°C / min, and held at 1350°C for 4 hours. The product was then etched in a 5 mol / L sodium hydroxide solution for 72 hours. After etching, the product was washed with deionized water by centrifugation until the pH was neutral, dried, and the hollow double-shell product was collected.

[0034] Figure 1 Scanning electron microscope (SEM) image of hollow double-shell SiC@C nanoparticles, from Figure 1 It can be seen that the diameter of the spheres in the hollow double-spherical shell SiC@C is distributed between 250nm and 290nm.

[0035] Figure 2 The image shows the XRD pattern of the hollow double-shell SiC@C nanoparticles. Combined with the XRD standard card, it can be seen that the SiC@C composite nanoparticles were successfully synthesized.

[0036] Step 3: Place 30 mg of the hollow double-shell obtained in Step 2, 0.606 g of ferric nitrate nonahydrate, 0.218 g of cobalt nitrate hexahydrate, and 0.472 g of citric acid monohydrate in 50 ml of deionized water. Add ammonia to adjust the pH to 9-10. After stirring for 20 min, place the mixture in a 100 ml polytetrafluoroethylene liner for hydrothermal reaction. The hydrothermal reaction temperature is 200℃, and the hydrothermal holding time is adjusted to 8 h. After the hydrothermal reaction is completed, wash the mixture three times with deionized water and once with alcohol. Dry the mixture in an oven to obtain the hollow double-shell silicon carbide@carbon@metal oxide composite material.

[0037] Step 4: Place the hollow double-shell silicon carbide@carbon@metal oxide composite material obtained in Step 3 into a high-temperature tube furnace and heat it from room temperature to 800℃ at a heating rate of 2℃ / min. Hold it at 800℃ for 2 hours. Utilize the reducing properties of the outer carbon shell to reduce the outer metal oxide to FeCo alloy nanoparticles, and finally obtain the hollow double-shell ternary composite nano-absorbing material SiC@C@FeCo.

[0038] Figure 3 This is a high-magnification transmission electron microscope (TEM) image of the hollow double-spherical shell ternary composite nanomaterial SiC@C@FeCo. The image shows that the prepared nanospheres have a hollow structure, and the total shell thickness is approximately 20 nm. Furthermore, compared to… Figure 1 , Figure 3 The nanoparticles embedded on the surface of the spherical shell are metallic iron-cobalt nanoparticles.

[0039] Figure 4 The image shows the XRD pattern of the hollow double-spherical shell ternary composite nano-absorbing material SiC@C@FeCo. As can be seen from the XRD standard card, the characteristic peaks of FeCo alloy appear, indicating that the SiC@C@FeCo ternary composite nano-absorbing agent has been successfully synthesized.

[0040] Example 3

[0041] This embodiment provides a ternary composite nano-absorbing material with a hollow double-spherical shell structure. The preparation method includes the following steps:

[0042] Step 1: Place 4.56 ml of tetraethyl silicate in a solution containing 100 ml of anhydrous ethanol, 14 ml of deionized water, and 6 ml of ammonia and stir for 25 min. Then, completely dissolve 0.8 g of resorcinol in 4.48 ml of formaldehyde solution (37 wt%) and add it to the solution containing tetraethyl silicate. Continue stirring and reacting for 24 h. The resulting organic solution is washed three times by centrifugation with deionized water and three times by centrifugation with ethanol to obtain the organic precursor.

[0043] Step 2: The organic precursor obtained in Step 1 was placed in a tube furnace and heated from room temperature to 550°C at a rate of 2°C / min, and held at 550°C for 2 hours. Then, the temperature was increased from 550°C to 1350°C at a rate of 2°C / min, and held at 1350°C for 4 hours. The product was then etched in a 5 mol / L sodium hydroxide solution for 72 hours. After etching, the product was washed with deionized water by centrifugation until the pH was neutral, dried, and the hollow double-shell product was collected.

[0044] Step 3: Place 30 mg of the hollow double-shell obtained in Step 2, 0.606 g of ferric nitrate nonahydrate, 0.218 g of cobalt nitrate hexahydrate, and 0.472 g of citric acid monohydrate in 50 ml of deionized water. Add ammonia to adjust the pH to 9-10. After stirring for 20 min, place the mixture in a 100 ml polytetrafluoroethylene liner for hydrothermal reaction. The hydrothermal reaction temperature is 200℃, and the hydrothermal holding time is adjusted to 12 h. After the hydrothermal reaction is completed, wash the mixture three times with deionized water and once with alcohol. Dry the mixture in an oven to obtain the hollow double-shell silicon carbide@carbon@metal oxide composite material.

[0045] Step 4: Place the hollow double-shell silicon carbide@carbon@metal oxide composite material obtained in Step 3 into a high-temperature tube furnace and heat it from room temperature to 800℃ at a heating rate of 2℃ / min. Hold it at 800℃ for 2 hours. Utilize the reducing properties of the outer carbon shell to reduce the outer metal oxide to FeCo alloy nanoparticles, and finally obtain the hollow double-shell ternary composite nano-absorbing material SiC@C@FeCo.

[0046] The hollow double-spherical shell ternary composite nano-absorbing material SiC@C@FeCo prepared in Example 2 was mixed with paraffin (mass ratio 3:7) to prepare a sample for testing its absorption performance. The absorption performance results at different matching thicknesses are as follows: Figure 5 As shown in the figure, the sample achieves an excellent absorption bandwidth of 6.21 GHz with a thickness of 1.98 mm, and its electromagnetic wave loss capability reaches a high intensity of -62 dB with a matching thickness of 4.61 mm.

[0047] In this invention, unless otherwise stated, scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. Furthermore, the reagents, materials, and procedures used herein are all widely used in the relevant fields.

[0048] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a ternary composite nano-absorbing material with a hollow double-spherical shell structure, characterized in that: Includes the following steps: Step 1: Prepare an organic precursor of carbon source coated with silicon source by placing tetraethyl silicate and resorcinol in an alkaline solution environment to undergo a sol-gel process; the ratio of tetraethyl silicate to resorcinol is 4~6 ml : 0.5~1 g; Step 2: Carbonize the organic precursor obtained in Step 1 under high temperature and inert gas, and etch the carbonized product with sodium hydroxide solution to obtain a hollow double spherical shell. Step 3: Combine the hollow double-spherical shell obtained in Step 2 with Fe 3+ and Co 2+ Mix, add citric acid to Fe 3+ and Co 2+ Complexation was performed, and then the pH was adjusted to 9-10, followed by a hydrothermal reaction to obtain a hollow double-shell silicon carbide@carbon@metal oxide composite material; the hydrothermal reaction was carried out at a temperature of 180-250℃ for 4-12 hours; the Co... 2+ and Fe 3+ They are cobalt nitrate nonahydrate and ferric nitrate hexahydrate, respectively; citric acid is citric acid monohydrate; Fe 3+ Co 2+ The molar ratio of citric acid monohydrate to citric acid monohydrate is 2:1:3; Hollow double shell and Fe 3+ The dosage ratio is 20~40mg : 0.0015mol; Step 4: The hollow double-shell silicon carbide@carbon@metal oxide composite material obtained in Step 3 is subjected to a carbothermic reduction reaction to finally obtain the hollow double-shell ternary composite nano-absorbing material SiC@C@FeCo. The specific method for the carbothermic reduction reaction is to raise the temperature from room temperature to 800℃ at a heating rate of 2℃ / min, and then hold it at 800℃ for 2 hours.

2. The preparation method of the ternary composite nano-absorbing material with a hollow double-spherical shell structure according to claim 1, characterized in that: in, The specific method for step one is as follows: place tetraethyl silicate in a solution containing anhydrous ethanol, deionized water and ammonia and stir for 20-40 minutes. Then dissolve resorcinol in formaldehyde solution and add it to the solution containing tetraethyl silicate. Continue stirring for 20-30 hours to obtain the organic precursor.

3. The method for preparing the ternary composite nano-absorbing material with a hollow double-spherical shell structure according to claim 1, characterized in that: in, In step two, the specific method of carbonization is as follows: the temperature is increased from room temperature to 550°C at a rate of 2°C / min, and held at 550°C for 2 hours; then the temperature is increased from 550°C to 1350°C at a rate of 2°C / min, and held at 1350°C for 4 hours.

4. The method for preparing the ternary composite nano-absorbing material with a hollow double-spherical shell structure according to claim 1, characterized in that: in, In step two, the concentration of the sodium hydroxide solution is 5 mol / L, and the etching time is 72 h.

5. A ternary composite nano-absorbing material with a hollow double-spherical shell structure prepared by the preparation method according to any one of claims 1 to 4.

6. The application of the ternary composite nano-absorbing material with a hollow double-spherical shell structure as described in claim 5 in microwave absorption.

Citation Information

Patent Citations

  • Wave-absorbing powder material as well as preparation method and application thereof

    CN113214787A

  • Corrosion-resistant wave-absorbing composite material and preparation method thereof

    CN115484806A